Influence of Overcharge Abuse on the Thermal-Electrochemical Performance of Sodium Ion Cells - Jiangyun Zhang; Ruli Zhang; Fei Duan; Mingli Niu; Guoqing Zhang; Ting Huang; Xiaoyong Wang; Yuliang Wen; Ning Xu; Xin Liu (Energies, 2025)
Thermal safety issues of sodium-ion batteries have become a major challenge, particularly under abusive conditions where the risk of thermal runaway is heightened. This study investigates the effects of overcharging on the thermal safety of sodium-ion batteries. Discharge capacity and time, internal resistance, and electrochemical impedance spectroscopy (EIS) at different states of charge (SOCs) are analyzed. Additionally, heat generation behaviors are evaluated at both normal/elevated temperatures. It is found that the overcharged batteries (OBs) demonstrate a significant increase in internal resistance from 46.72 Ω to 65.99 Ω. The discharge time of OBs at 1 C current (the ratio of the rate at which a battery discharges per unit time to its rated capacity) is reduced by 4.26% compared to normal batteries (NBs). The peak temperature and temperature difference increase by 5.6% and 36.1%, respectively. When discharged at 1 C at 40 °C, OBs have a 5.47% reduction in discharge time compared to NBs. Furthermore, the OBs exhibit an increase in the peak discharge temperature and temperature difference of 0.99 °C and 0.4 °C, respectively. Microscopic analysis of the electrode materials makes clear the irreversible damage to the internal structures of the sodium-ion battery caused by overcharging. This study potentially provides fundamental data support and theoretical insights for sodium-ion battery module thermal safety.